The International Academy of Health Sciences Informatics (IAHSI): IMIAs Academy is Now Established and on Track - Haux, Reinhold; Ball, Marion J.; Kimura, Michio; Martin-Sanchez, Fernando; Otero, Paula; Huesing, Elaine; Koch, Sabine; Lehmann, Christoph U. (Yearbook of Medical Informatics, 2020)
Objectives: To summarize the major activities of the International Academy of Health Sciences Informatics (IAHSI) from 2018 until 2019, and to provide an outline of actions planned for 2020.Method: Reporting about these activities and actions by the members of the Academy's first Board.Results: Academy bylaws were accepted by the Academy Plenary and the IMIA General Assembly on August 25th, 2019 and August 26th, 2019, respectively. Academy's strategy and focus areas were developed. Based on the Academy's eligibility criteria, the 2018/2019 Class made of 26 new Academy Fellows was elected. Future activities will concentrate on building taskforces for developing and implementing major Academy focus areas.Conclusions: We are glad to report that the Academy is strong and thriving.
Keywords: Biomedical and health informatics; medical informatics; health informatics; Academy of Sciences; International Academy of Health Sciences Informatics